Mothers' knowledge about complementary feeding - Lea Masan; Yunida Haryanti; Rizki Amartani; Yolanda Montessori; Paskalia Kurniati; Hearty Efifania Ose Payon; Asri Fitri Yati (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: According to WHO data (2020), 40% of infants worldwide are exclusively breastfed, and 60% of infants are given complementary foods before the age of 6 months. According to data from the 2021 Basic Health Research in Indonesia, 52.5% or just half of the 2.3 million infants under 6 months of age are exclusively breastfed, and some children are already being given complementary foods before 6 months of age. Eight out of 10 people interviewed did not understand complementary feeding. Purpose: To determine the level of mothers’ knowledge regarding complementary feeding for infants aged 6-24 months. Mothod: This study used a quantitative descriptive method with 40 mothers as respondents and univariate analysis. It was found that 43% of respondents had good knowledge of complementary feeding for infants aged 6-24 months. Thirty-eight percent of respondents had adequate knowledge, and a small portion 20% had insufficient knowledge regarding complementary feeding for children aged 6-24 months. Results: The respondents had good knowledge regarding the provision of complementary feeding for infants aged 6–24 months, with a percentage of 43%. Conclusion: Respondents’ knowledge of complementary feeding for infants aged 6–24 months is generally good, particularly regarding the types and purposes of complementary feeding. Suggestion: It is hoped that health departments and midwives will consistently provide education to new mothers to ensure they pay attention to complementary feeding, starting with the texture and nutritional needs appropriate for the infant’s age.